Shift to Digital Audit: A Study Investigating the Benefits and Challenges of Digitalization on the Audit Profession - Angeles, Earl Jed A. Angeles; Mabazza, Godfrey B. Mabazza; Pascua, Angel Errine Grace B. Pascua; Salta, Krishabelle E. Salta; Santiago, Zedric Joel V. Santiago; Marquez, Jerome Marquez; Catacutan, Karen Joy (Asian Journal of Management Analytics, 2023)
This study intends to evaluate the perceived benefits and challenges that these technologies offer in the context of digitalization, to one of the most suitable professions for the particular procedure; the audit profession.  A qualitative study was conducted to gain a better grasp of the implications of digitalization on audit tools in the audit profession. This is accomplished by conducting ten (10) semi-structured interviews with professional auditors, emphasizing interpretation. It has been found that this study backs up some of the conclusions of prior research on the issue of digital auditing. Conclusively, the empirical findings of this study support the assumption that auditors believe digitalization will become even more popular in the future and that it will not result in job losses, as prior studies have suggested.